Preparation and characterization of a transparent amorphous cellulose film. Issue 4 (10th December 2014) - Zhang, Bo-xing; Azuma, Jun-ichi; Uyama, Hiroshi
Abstract : Amorphous cellulose film (ACF) was prepared from cellulose solution in lithium chloride (8 wt%)/ N, N -dimethylacetamide by regeneration with acetone. Abstract : Amorphous cellulose film (ACF) was prepared from cellulose solution in lithium chloride (8 wt%)/ N, N -dimethylacetamide by regeneration with acetone. The obtained ACF possessed a dense, smooth surface, and excellent transparency. The X-ray diffraction results indicated that ACF was highly amorphous, which was further confirmed by solid-state 13 C-NMR and Fourier transform infrared (FT-IR) spectra. The tensile analysis implied that the elongation at break (23.9%) and the maximum stress (157 MPa) of ACF derived from the Whatman CF11 fibrous cellulose were higher than those of cellophane (19.9% and 135 MPa, respectively). In addition, the enzymatic hydrolysis of ACF and cellophane showed that the former had a higher hydrolysis rate (about 7 times higher than the latter), indicating its outstanding environmental friendliness. This work provides a simple, less-destructive, and universal method to prepare transparent ACF, which could serve as a promising packaging material to replace cellophane.